2005
DOI: 10.1016/s0002-9440(10)61243-6
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Regulation of Epithelial Tight Junction Proteins Enhances Barrier Function and Blocks Enterohemorrhagic Escherichia coli O157:H7-Induced Increased Permeability

Abstract: Enterohemorrhagic Escherichia coli O157:H7 (EHEC) is an enteric pathogen that causes potentially fatal symptoms after intimate adhesion, modulation of intestinal epithelial signal transduction, and alteration of epithelial function (eg, barrier disruption). Although the epithelial barrier is critical to gut homeostasis, only a few agents, such as transforming growth factor (TGF)-beta, can enhance or protect epithelial barrier function. Our aims were to delineate the mechanism(s) behind TGF-beta-induced barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
162
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 48 publications
13
162
1
1
Order By: Relevance
“…The findings in the present study show that, similar to other intestinal pathogens (18,21), C. jejuni infection inflicts changes in epithelial barrier function, thereby leading to potential exposure of the subepithelial immune components to chronic antigenic stimulation. Such changes in epithelial permeability are well documented in humans with IBD (13), to which C. jejuni infection has been linked (2,5,6).…”
Section: Discussionsupporting
confidence: 51%
“…The findings in the present study show that, similar to other intestinal pathogens (18,21), C. jejuni infection inflicts changes in epithelial barrier function, thereby leading to potential exposure of the subepithelial immune components to chronic antigenic stimulation. Such changes in epithelial permeability are well documented in humans with IBD (13), to which C. jejuni infection has been linked (2,5,6).…”
Section: Discussionsupporting
confidence: 51%
“…52 In vitro studies have indicated that the proallergic cytokine IL-4 contributes to barrier impairment in contrast with TGF-b, which enhances the barrier function and activates the expression of proteins comprising intercellular junctions. 53 In our study, the improvement of the gut barrier in the Lmix-colonized mice was accompanied by the reduced secretion of pro-allergic cytokines and the significant enhancement of TGF-b.…”
Section: Discussionsupporting
confidence: 50%
“…Exposure of MDCK cells to TGF-␤1 significantly increased claudin-1 and ZO-2 expression, correlating with the effect of CsA on these tight junction components, which further strengthens our hypothesis that CsA regulates tight junction function, at least partially, via this cytokine. Another study (37) demonstrated that TGF-␤ upregulated claudin-1 expression two-to three-fold in T84 monolayers, but expression of claudin-2 and claudin-4 was unaltered. In addition, we found that treatment of MDCK cells with the MEK 1 inhibitor U0126 decreased claudin-1 expression compared with control level (data not shown).…”
Section: Discussionmentioning
confidence: 98%